The use of indicators of life quality for public policies decision (Polis (Santiago), 2018)
The origins of the t quality of life concept goes back to the 1930’s and to the British economist Pigou, in his study on quantifying the services or social costs of government decisions, to be able to come up with a net social product.  Since that moment till now, the concept has been used with different significations until finally, during the 90’s decade, the concept was defined considering its subjective and objective dimensions. This article presents a multidimensional view of the concept quality of life and considers the possible relations with the concept public policies. Finally presents the necessity of considering the use of quality of life indicators which consider citizens opinions and perceptions of their vital situation, in order to take them in account when taking decisions of public policies.
Keywords: public policies; quality of life; indicators